Individual Differences in Human-Agent Teaming: An Analysis of Workload and Situation Awareness through Eye Movements. (September 2014) - Wright, Julia L.; Quinn, Stephanie A.; Chen, Jessie Y.C.; Barnes, Michael J.
Studies investigating the effects of level of autonomy (LOA) on workload and performance in human-agent teams typically utilize subjective measures, but do not often incorporate physiological measures. This paper examines how well eye movement data collected in a recent experiment converges with the findings suggested by the subjective measures. Several eye behavior measures (fixation count, average fixation duration, blink rate, saccade amplitude and pupil diameter) were evaluated, and findings based on these compared to findings of NASA-TLX and situation awareness questionnaires. In addition, individual differences due to perceived attentional control were evaluated. Findings indicate that the physiological measures account for variance in workload that typical subjective measures may not, as they are more sensitive to individual differences among participants.